Phomeketales A–F, six unique metabolites from the endophytic fungus Phoma sp. YN02-P-3. Issue 69 (8th July 2016) - Sang, Xia-Nan; Chen, Shao-Fei; Chen, Gang; An, Xiao; Li, Sheng-Ge; Li, Xiao-Ni; Lin, Bin; Bai, Jiao; Wang, Hai-Feng; Pei, Yue-Hu
Abstract : Phomeketales A–F (1–6 ), six new xyloketals, with unprecendented carbon substitution at C-16 and C-17 simultaneously, were isolated from the endophytic fungus Phoma sp. YN02-P-3. Abstract : Phomeketales A–F (1–6 ), six new xyloketals, with unprecendented carbon substitution at C-16 and C-17 simultaneously, were isolated from the endophytic fungus Phoma sp. YN02-P-3. Their structures were elucidated on the basis of 1D and 2D NMR spectral data and ECD analysis. Compound 3 exhibited moderate anti-AChE activity and cytotoxicity against HL-60.